Analysis of Determinants Associated with the Activeness of Posyandu Cadres in the Working Area of the Tarus Health Center, Kupang Tengah Sub-District, Kupang District - Viana, Carmen; Ribka Limbu; Marni Marni (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Background: The activeness of cadres is very important in Posyandu activities because if cadres are not active then the provision of health services and Posyandu activity programs cannot run well, so cadre coaching is needed by health workers to increase the active role of cadres in the implementation of Posyandu activities. Purpose: This study aims to analyze the determinants associated with the activeness of Posyandu cadres in the working area of Puskesmas Tarus, Kupang Tengah District, Kupang Regency in 2024. Methods: This type of research is an analytic survey with a cross sectional research design. The sample in this study were 71 people. Sampling in this study using simple random sampling technique with a level of significance ? = 0.05. Results: The results showed that there was a relationship between the variables of knowledge (p=0.000), attitude (0.002) and training 0.002 with the activeness of Posyandu cadres in the working area of the Tarus Health Center, Kupang Tengah District, Kupang Regency. Conclusion: It is expected that health workers at the Tarus Health Center should always maintain the implementation of cadre training by providing counseling on the importance of activeness of Posyandu cadres so that Posyandu activities can run well, and it is also expected that Posyandu cadres can increase activeness as a social responsibility in the community.